87 Opioid deprescribing in people with chronic non-cancer pain – a systematic review of international guidelines. (4th December 2019) - Lin, Christine; Kwok, Wing Shan; Hsieh, Arielle; Ballantyne, Jane; Blyth, Fiona; Deyo, Rick; Korff, Michael von; Gnjidic, Danijela
Abstract : Objectives: Overuse of prescription opioid analgesics is a major international public health problem. The objectives of this review are to i) investigate guideline recommendations on opioid deprescribing in people with non-cancer pain, ii) compare these recommendations across international guidelines, and iii) rate the risk of bias of the guidelines. Methods: We searched electronic databases from inception to December 2018 for opioid guidelines containing recommendations to deprescribe (taper or stop) the use of prescription opioid analgesics in people with chronic non-cancer pain. There was no language or publication restriction. We also consulted experts and performed citation tracking. Screening and data extraction were conducted by two independent reviewers following standard methodology, and the risk of bias was assessed using the AGREE II tool. The outcomes, i) when to deprescribe, ii) how to deprescribe, iii) managing withdrawal symptoms, iv) additional support during the deprescribing process, v) monitoring outcomes and vi) deprescribing in patients with co-prescription of sedatives, were presented descriptively. Results: The search resulted in 2905 unique references and 7 included guidelines: 4 from America, 1 from Australia, 1 from Canada and 1 from Germany. All deprescribing recommendations were embedded within prescribing guidelines rather than presented in a standalone deprescribing guideline. In general, guidelines scored well in all risk of bias domains on AGREE II except for applicability (limited information on guideline monitoring or auditing). We are currently finalising data interpretation; preliminary results are presented below. For when to deprescribe, all 7 guidelines recommended deprescribing in cases where benefits were outweighed by harms, and in pregnant women or those at a higher risk (e.g. substance use disorder). One guideline made specific recommendations on post-surgical patients. For how to deprescribe, some guidelines recommended a tapering plan at the time of opioid initiation, and gave guidance on the speed of tapering but this varied between 5% to 25% per week in different clinical situations and between guidelines. Two guidelines did not provide specific recommendations on managing withdrawal symptoms, while other guidelines recommended patient and family education, a slower taper, and specific medicines to manage symptoms such as nausea. For additional support, one guideline provided no recommendations but the most common support recommended by other guidelines included mental health support, multidisciplinary team involvement (e.g. for non-pharmacological pain management and pharmacy) and pain or addiction specialists. Recommendations on outcome monitoring varied between guidelines. Some recommended regular monitoring, and some recommended pausing or discontinuing the deprescribing process if appropriate (e.g. substantial increase in pain). Four guidelines made specific recommendations on co-prescription with sedatives, all recommending against the concurrent use of these medicines and for the gradual tapering of both medicines. Conclusions: Opioid deprescribing recommendations are being made in opioid prescribing guidelines. In general there is consistency in when and how to deprescribe, but fewer recommendations are offered on managing withdrawal symptoms, outcome monitoring and co-prescription with sedatives.